Fisher, Neyman, and the Creation of Classical Statistics - Lehmann, Erich L. (Springer New York : Imprint: Springer, 2011)
Classical statistical theory-hypothesis testing, estimation, and the design of experiments and sample surveys-is mainly the creation of two men:  Ronald A. Fisher (1890-1962) and Jerzy Neyman (1894-1981).  Their contributions sometimes complemented each other, sometimes occurred in parallel, and, particularly at later stages, often were in strong opposition.  The two men would not be pleased to see their names linked in this way, since throughout most of their working lives they detested each other.  Nevertheless, they worked on the same problems, and through their combined efforts created a new discipline. This new book by E.L. Lehmann, himself a student of Neyman's, explores the relationship between Neyman and Fisher, as well as their interactions with other influential statisticians, and the statistical history they helped create together. Lehmann uses direct correspondence and original papers to recreate an historical account of the creation of the Neyman-Pearson Theory as well as Fisher's dissent, and other important statistical theories.